THE ANALYSIS OF RICHARD A VIAS NEVER ON WEDNESDAY BASED ON BROWN AND LEVINSON’S POLITENESS STRATEGIES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The purpose of this study was to identify politeness strategies found in the script of a play, Never On Wednesday, written by Richard A. Via. This analysis was based on Brown and Levinson’s theory about politeness strategies. The subject of this study was the exchange between the character Fred, Father, and Mother. Based on the findings, it was found that there are four politeness strategies in this play, namely bald on record, positive politeness, negative politeness, and off-record strategy. There is no don’t-do-the-act strategy in this play because each character keeps talking and not being silent. Further research about politeness strategies in drama needs elaborating more.